The role of discrete negative emotions in predicting the behavior of misusing time and resources in business organization - Savitha, J.; Akhilesh, K.B. (University of Sri Jayewardenepura, 2018)
Counterproductive work behaviors (CWB) are the deviant behaviors of employees that violate the organizational norms, and in turn harm the organization or its members. Misuse of time and resources, a form of CWB is of increasing concern to business organisations worldwide. Such behaviors are mainly aimed at organizations than the individuals, restricting productive time on the job and inappropriate or unauthorized use of organisational resources. Extant literature informs that these behaviors are caused by stressful work conditions mediated by negative emotions. However, the extant literature does not adequately consider multiple discrete emotions to study CWB. This study examines the influence of discrete negative emotions on CWB in the context of manufacturing and IT firms in India. It contributes to theory by linking individual emotions to the deviant behaviors relevant to misuse of time and resources. Finally, the managerial implications derived from the study helps to understand employees’ emotional states and their possible consequences.
Keywords: misuse of time and resources, counterproductive work behavior, time theft, time banditry, withdrawal